2023
DOI: 10.3390/vaccines12010037
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Titer and Broad Anti-SARS-CoV-2 Neutralization Induced by Stabilized RBD Nanoparticles from Strain BA.5

Zhantong Wang,
Baoshan Zhang,
Li Ou
et al.

Abstract: The receptor-binding domain (RBD) of the SARS-CoV-2 spike is a primary target of neutralizing antibodies and a key component of licensed vaccines. Substantial mutations in RBD, however, enable current variants to escape immunogenicity generated by vaccination with the ancestral (WA1) strain. Here, we produce and assess self-assembling nanoparticles displaying RBDs from WA1 and BA.5 strains by using the SpyTag:SpyCatcher system for coupling. We observed both WA1- and BA.5-RBD nanoparticles to degrade substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Using the EnDS, RBDs of SARS-CoV-2 isolates from WA1 and BA.5 carrying RBDstabilizing mutations were displayed via spyTag/SpyCatcher system to generate individual or mosaic NPs. The NPs were shown to induce significantly higher homologous and heterologous neutralizing titers [115] in mice. Interestingly, the study revealed that these vaccines can also elicit higher neutralizing antibody titers against other β-coronaviruses [115].…”
Section: CII Viral Vaccines With Encapsulin-based Np Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the EnDS, RBDs of SARS-CoV-2 isolates from WA1 and BA.5 carrying RBDstabilizing mutations were displayed via spyTag/SpyCatcher system to generate individual or mosaic NPs. The NPs were shown to induce significantly higher homologous and heterologous neutralizing titers [115] in mice. Interestingly, the study revealed that these vaccines can also elicit higher neutralizing antibody titers against other β-coronaviruses [115].…”
Section: CII Viral Vaccines With Encapsulin-based Np Platformmentioning
confidence: 99%
“…The NPs were shown to induce significantly higher homologous and heterologous neutralizing titers [115] in mice. Interestingly, the study revealed that these vaccines can also elicit higher neutralizing antibody titers against other β-coronaviruses [115].…”
Section: CII Viral Vaccines With Encapsulin-based Np Platformmentioning
confidence: 99%
“…Using the EnDS, the RBDs of SARS-CoV-2 isolates from WA1 and BA.5 carrying RBD-stabilising mutations were displayed via the spyTag/SpyCatcher system to generate individual or mosaic NPs. The NPs were shown to induce significantly higher homologous and heterologous neutralising titers [ 117 ] in mice. Interestingly, the study revealed that these vaccines can also elicit higher neutralising antibody titers against other β-coronaviruses [ 117 ].…”
Section: Vaccine Platforms Utilising Various Pnpsmentioning
confidence: 99%
“…The NPs were shown to induce significantly higher homologous and heterologous neutralising titers [ 117 ] in mice. Interestingly, the study revealed that these vaccines can also elicit higher neutralising antibody titers against other β-coronaviruses [ 117 ].…”
Section: Vaccine Platforms Utilising Various Pnpsmentioning
confidence: 99%